KAJIAN KONSEP PEMBINAAN NARAPIDANA (Studi Kasus di LAPAS wanita Kelas IIA Semarang). - Soerjowinoto, Petrus (VITASPHERE, 2012)
Guidance toward the female prisoners in the penitentiary institution is based on: age. sex and the length of the sanction. as well as other criteria or the development needed for the guidance. which requires special treatment. The purposes and importance of this research are: (J) to find out all of the elements that influence . the whole process of the prisoners guidance. (2) to discover all the uncovered needs during the guiding time and also discover the guidance model as an alternative. The method that is used in this research is ridical sociological with the specification of descriptive analysis. Based on the result 0 research and discussion. it can be concluded that the elements which influence the pris ers guidance contains four things: self,family. community and the officer. The all four el ments are connected each other. The needs that are not well accommodated in the implementation of prisoners guidance are: a) The prisoner who do not have any family that ar lling to guarantee. b) The management of stress. depression,fear that are experience Py the prisoners in the time when the prisoners will be free have not been accommodated. uggestion: it is necessary to create an institution and shelter for the ex-prisoners. includng the psychologists. SOciologists. spirituals. and other experts to do the healing